Diplomatic Services Today: Between Political Decisions and Administrative Criteria - Valentin NAUMESCU (Transylvanian Review of Administrative Sciences, 2015)
As a highly specialized and relatively small sized public service (in terms of staff and bud-get), diplomacy has always been in a particular position within the administrative system of most countries. Not only does diplomacy attract the pretended ‘elites’ of the public sector’s employ-ees but also a lot of popular criticism with regard to its performances, transparency, dedication to public interest, procedures of recruitment, privileges, and sometimes moral exigencies. This paradoxical ambivalence of ‘elitism’ and public distrust coexists with variable degrees of tension between politicization and the need of effective technocracy. This article explores the concepts, delimitations and functioning of the po-litical-ideological vs. administrative components of diplomatic systems, in the wider context of the administrative paradigms and political cultures to which they belong. While the theoretical distinc-tion between foreign policy and diplomacy is way more developed in European classical approach-es, though with controversial results, the Ameri-can authors and offcials traditionally use the two concepts interchangeably. Notwithstanding this theoretical fexibility, the borderline between the political level of diplomatic representation and the professional diplomatic and consular corps is clearer and better regulated in the U.S. sys-tem than in most of the European countries. A case study focused on the reform of the Roma-nian diplomatic service, in the pre- and post-EU accession years, serves as empirical analysis of this demarche.